Pemanfaatan Cangkang Telur Sebagai Pupuk Organik Pada Tanaman di Desa Gebang Kabupaten Pesawaran - Yulianty Soeradji; Endang Linirin Widiastuti; Endah Setyaningrum; Lili Chrisnawati (CV. Multi Kreasi Media, 2023)
−Eggshells are one of the organic waste that is commonly found and comes from households. Based on observations in the field, people generally have not done waste management properly such as separating organic and inorganic waste. However, the utilization of household waste in the form of eggshells has not been widely done by the community. The solution to overcome this problem is to conduct training for the community to utilize waste in the form of eggshells to be used both for nurseries and further processing as organic fertilizer to increase plant growth. The desired expectation in the implementation of this service is an increase in skills and knowledge in making organic fertilizer from eggshells. There was an increase in knowledge and skills of the service participants with a pretest score of 55.88 and post-test to 90.00. There was an increase in value of 34.12. The percentage increase in value is 62.86%.